The role of women rebel returnees in the armed conflict and transformative politics in Leon, Iloilo - Apatan, Mildred Villena
The study focuses on the role of the women rebel returnees in the armed conflict and transformative politics in Leon. Descriptive in nature, it pioneers in the study of women rebel returnees in the region. It has the following objectives: to determine the reasons of the women rebel returnees for joining the insurgency movement, to determine the nature of their political participation and role in the armed conflict, to identify the reasons which brought them back into the mainstream of society, and to describe the role they played in transformative politics. The method used in gathering the data was personal interview with an interview guide. Also, a questionnaire on their socio demographic profile was provided. The study found out that, in general, the women rebel returnees joined the insurgency movement for social reasons such as influence of those who were already members of the movement. Their role inside the movement was mostly reproductive in nature, that is, works that deals mostly with or involves their comrades and the movement. Their reasons for leaving the movement were also socially motivated. Their participation in transformative politics is also reproductive in nature and that their positions in various organizations and institutions belong to a relatively upper level. Their problem are mostly financial and could be addressed by giving them more projects, opportunities, and network with other women's organizations.